Working capital management and firm's profitability: Evidence from Czech certified firms from the EFQM excellence model - Muhammad Yousaf; Petr Bris; Ismat Haider (Cogent Economics & Finance, 2021)
Working capital management (WCM) is one of the most important decisions for all firms. The main components of WCM are days sales outstanding (DSO), days inventory outstanding (DIO), days payable outstanding (DPO), and cash conversion cycle (CCC). Using a sample of 332 Czech firms, including 20 certified firms from the EFQM (European Foundation for Quality Management) Model, the current study explored the effects of the main components of WCM on firms' profitability. We used two different regression models to test the hypothesis, i.e. pooled regression and maximum likelihood estimation (MLE). The findings of the research revealed all the components of WCM have a negative impact on firm profitability. On the other hand, the interaction terms of the EFQM certified firms with the components of WCM showed a positive impact on firms' profitability which means that there is a positive relationship between the components of WCM of the certified firms and profitability. However, it is examined that the quality certificate/award from EFQM Excellence Model decreases the firm's profitability. The outcomes of the current research will be beneficial to academics, managers, leaders, and directors of the firms to improve their firm's profitability.
Keywords: 330; CCC; Czech firms; EFQM; firm profitability; working capital